FINANCIAL MANAGEMENT BEHAVIOR AMONG STUDENTS: THE INFLUENCE OF DIGITAL FINANCIAL LITERACY - Clarence, Johann; Pertiwi, Dewi (Petra Christian University, 2023)
The goal of this study is to investigate how digital financial literacy affects the financial management behavior of students who use digital banking services in Surabaya. Primary data were obtained from questionnaires distributed to students in Surabaya. Using the SmartPLS 4 program, the partial least square structural equation modeling (PLS-SEM) technique was employed for data analysis in this study. The findings of this study indicate that students in Surabaya who utilize digital banking services have a substantial impact on their saving behavior when they are financially literate, digital financial literacy has a significant effect on the spending behavior of students who use digital bank services in Surabaya, digital financial literacy has a significant effect on investment behavior of students who use digital bank services in Surabaya. In short, this research can contribute to helping students in Surabaya to deepen their understanding of digital financial literacy.